ECOLOGICAL SIGNIFICANCE OF LITHOGEOCHEMICAL EXPLORATION METHODS FOR ORE DEPOSITS (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Geochemical anomalies of trace elements of both geogenic and technogenic origin occur in soils distributed in various ore fields. The distribution patterns of element concentration in soils are primarily influenced by the bedrock with different types of endogenic geochemical anomalies, and by the soil forming processes, which modify the basic geochemical composition and redistribute the content of metals within the soil profile. Alteration processes may lead to the release of potentially toxic elements, particularly heavy metals, into the environment.
Keywords: geogenic and technogenic anomalies; soil profile; bedrock; ore field